A green method for the synthesis of coumarin dye and its application to hypochlorite recognition. (May 2022) - Zhang, Yanting; Huang, Yongfei; Huo, Fangjun; Zhao, Changqing; Yin, Caixia
Abstract: In modern organic synthesis, green organic synthesis technology has become an important research direction in the field of chemistry and chemical engineering. Coumarin dyes play an important role in industrial chemistry, biochemistry and material science, so the synthesis of fluorescent dyes has been an important problem in modern organic synthesis. Therefore, the design and discovery of green organic synthesis of coumarin derivatives is very important. Hypochlorous acid/hypochlorite as a ROS plays an important role in diagnosis and treatment of diseases. To date, many probes have been developed for HClO/ClO − detection. Among them, some probes have poor selectivity and slow response time for HClO/ClO −, which greatly limits the practical application value of probes. In this work, the reaction of 7-(diethylamino)-2H-chromene-2-thione with hypochlorite produces 7-(diethylamino)-2H-chromen-2-one, which is a novel green synthesis method of coumarin dye. The experimental results showed that the reaction is a ratiometric, selective and sensitive fluorescence system for the recognition of hypochlorite. This method has been successfully to detection of hypochlorite in HeLa/HNEpC cells, zebrafish and actual sample detection. Highlights: 7-(diethylamino)-2H-chromen-2-one was synthesized by a novel green organic synthesis method. The probe showed high selectivity and fast response (60 s) to ClO − in DMSO/PBS (v/v, 1/1, pH = 7.4) system. The probe with excellent performance showed good applications in cells, zebrafish and actual sample detection.